Interlinkage, limited liability, and strategic interaction - Basu, Kaushik (The World Bank, 1999)
June 1999 - When will a landlord prefer to supply both land and credit to a tenant rather than allow the lender to borrow from a separate moneylender? The paper shows that if tenancy contracts are obtained prior to contracting with the moneylender, and the tenant has limited liability, interlinked deals will predominate over the alternative situation where the landlord and the moneylender act as noncooperative principals. Basu, Bell, and Bose analyze the example of a landlord, a moneylender, and a tenant (the landlord having access to finance on the same terms as the moneylender). It is natural to assume that the landlord has first claim on the tenant's output (as a rule, if they live in the same village, he may have some say in when the crop is harvested). The moneylender is more of an outsider, not well placed to exercise such a claim. A landless, assetless tenant will typically not get a loan unless he has a tenancy. Without interlinkage, the landlord is likely to move first. In the noncooperative sequential game where the landlord is the first mover and also enjoys seniority of claims if the tenant defaults, interlinkage is superior, even if contracts are nonlinear - a result unchanged with the incorporation of moral hazard. The main result is that if a passive principal - one whose decisions are limited to exercising his property rights to determine his share of returns - is the first mover, allocative efficiency is impaired unless his equilibrium payoffs are uniform across states of nature. The limited liability of the tenant creates the strict superiority of interlinkage by making uniform rents nonoptimal when, with noncollusive principals, the landlord (the passive principal) is the first mover. A change in seniority of claims from the first to the second mover (the moneylender) further strengthens this result. But uniform payoffs for the first mover are not essential for allocative efficiency if he is the only principal with a continuously variable instrument of control. So, the main result is sensitive to changes in the order of play but not to changes in the priority of claims. This paper - a product of the Office of the Senior Vice President and Chief Economist, Development Economics - is part of a larger effort in the Bank to understand the institutional structure of rural markets and its welfare implications. The authors may be contacted at kbasuworldbank.org, clive.bell@urz.uni-heidelberg.de, or psbose@cc.memphis.edu